Inventory Planning with Method Q and Method P for Probabilistic Demand on Chrysanthemum Seeds at PT Transplants Indonesia - Sutoni, Akhmad; Taufik, Dani Hamdan (International Journal of Innovation in Enterprise System, 2018)
Fluctuating and uncertain demand is a problem faced by manufacturing firms. The problem can be mitigated by the availability of inventory systems. This inventory serves to ensure the availability of appropriate resources in the right quantity and at the right time, so as to minimize the costs incurred. PT. Transplants Indonesia is a company engaged in the business of chrysanthemum flower in Indonesia. PT. Transplants Indonesia is a subsidiary of Okinawa Flower Agricultural Cooperative Association (OKF) in Okinawa, Japan. The purpose of this company establishment is to meet the demand of farmers who are members of the OKF.  In the case of backorder, on Q method with probabilistic request the size of the lottery (Q) is always fixed for every time the order is made and the order is made if the amount of inventory has reached a certain level (r) called the reorder point. In method P with probabilistic order requests made according to a fixed interval of time (T) and the ordering does not exceed the maximum inventory limit (R). Total Inventory cost incurred by the company using the method used by the company amounted to Rp.74.995.360,84. The inventory model using the Q method generates a total inventory cost of Rp.70.253.291,46. Meanwhile, inventory model using P method resulted in total inventory cost of Rp.71.529.327,17. So economically, the selected inventory model is the inventory model with the Q method which has a lower total inventory cost value than using the P method.